Fyn-tau Ablation Modifies PTZ-Induced Seizures and Post-seizure Hallmarks of Early Epileptogenesis - Putra, Marson; Puttachary, Sreekanth; Liu, Guanghao; Lee, Gloria; Thippeswamy, Thimmasettappa (Frontiers in Cellular Neuroscience, 2020)
Both Fyn and tau have been associated with neuronal hyperexcitability and neurotoxicity in many tauopathies, including Alzheimer’s disease (AD). Individual genetic ablation of fyn or tau appears to be protective against aberrant excitatory neuronal activities in AD and epilepsy models. It is, however, still unknown whether ablation of both Fyn and tau can likely elicit more profound anti-seizure and neuroprotective effects. Here, we show the effects of genetic deletion of Fyn and/or tau on seizure severity in response to pentylenetetrazole (PTZ)-induced seizure in mouse models and neurobiological changes 24h post-seizures. We used Fyn KO (fyn-/-), tau KO (tau-/-), double knockout (DKO) (fyn-/-/tau-/-), and wild-type (WT) mice of the same genetic background. Both tau KO and DKO showed a significant increase in latency to convulsive seizures and significantly decreased the severity of seizures post-PTZ. Although Fyn KO did not differ significantly from WT, in response to PTZ, Fyn KO still had 36±8% seizure reduction and a 30% increase in seizure latency compared to WT. Surprisingly, in contrast to WT, Fyn KO mice showed higher mortality in <20 min of seizure induction; these mice had severe hydrocephalous. None of the tau-/- and DKO died during the study. In response to PTZ, all KO groups showed a significant reduction in neurodegeneration and gliosis, in contrast to WT, which showed increased neurodegeneration (especially, parvalbumin (PV)-GABAergic interneurons) and gliosis. DKO mice had the most reduced gliosis. Immunohistochemically, phospho-tau (AT8, pS199/S202), Fyn expression, as well as Fyn-tau interaction as measured by PLA increased in WT post-PTZ. Moreover, hippocampal Western blots revealed increased levels of AT8, tyrosine phospho-tau (pY18), and phosphorylated Src tyrosine family kinases (pSFK) in PTZ-treated WT, but not in KO, compared to respective controls. Furthermore, PV interneurons were protected from PTZ-induced seizure effects in all KO mice. The levels of inwardly rectifying potassium (Kir 4.1) channels were also downregulated in astrocytes in the WT post-PTZ, while its levels did not change in KO groups. Overall, our results demonstrated the role of Fyn and tau in seizures and their impact on the mediators of early epileptogenesis in PTZ model.